Photosynthetic Shutdown in Chlorella NC64A Associated with the Infection Cycle of Paramecium bursaria Chlorella Virus-1. - Seaton, GGR. (1995)
The effects of the algal virus Paramecium bursaria Chlorella virus-1 on the photosynthetic physiology of its host, Chlorella NC64A, was studied by observing changes in Chl fluorescence quenching and O2 exchange. Metabolic changes were calibrated against electron microscopic analysis of the morphological changes that occur during the infection cycle. It takes approximately 10 h from attachment of the virus to final lysis of the host cell, so a complete infection cycle can be observed continuously in one experiment. During the early stages of the infection cycle many rapid changes occurred in the host cell's metabolism and these were reflected in changes of photosynthetic and respiratory rates. The dramatic inhibition of photosynthesis in Chlorella NC64A cells by P. bursaria Chlorella virus-1 has facilitated the use of fluorescence quenching as an accurate measure of the first phase of viral infection (attachment and penetration of the host cell) and the extent to which a population of host cells is infected. Effects of temperature and cation requirement of the infection cycle are described. The relevance of our observations to the events observed during viral infection of higher plants is discussed.